Rethinking The Theory of Legal Flexibility (Three Divorce Law Outside Religious Courts) - Muhammad Nafi (PT. Global Pustaka Ilmiah, 2025)
This study aims to review the concept of legal flexibility in the context of the practice of triple divorce carried out outside the Religious Court in Indonesia. The main focus of this study is to present another side of the theory of legal flexibility in the issue of triple divorce law outside the religious court which until now has only been punished as one divorce. This study is library research. The results of the study indicate that the application of the results of collective ijtihad in a regulation that binds the Indonesian people, in the form of a rare opinion, has created legal turmoil in society. Judges who do not consider the occurrence of a divorce pronounced by a husband outside the court on the grounds that using the principle of divorce is complicated, are challenged by the social community who choose to follow the opinion of the majority of scholars. The application of the articles in the UUP and KHI must be reconsidered by judges by looking at the social conditions of the community where the parties to the case live. Judges have the right to decide with contra legem, so that legal justice and legal certainty are achieved in society.